EFFECT OF COMPETENCE AND AUDITOR INTEGRITY TO THE AUDIT QUALITY IN THE INSPECTORATE REGENCY OF SERANG (INSPEKTORAT KABUPATEN SERANG) - Verliani Dasmaran; Alpia Aliana Lukman (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2018)
Research Objective is to know how the auditor's competence and integrity of the auditor has to affect the quality of audit. The object of research is the district inspectorate attack. The population of the research is all civil servants (ASN) working on Inspectorate Serang regency, and samples of research taken in this research are as many as 32 (thirty two) people, with purposive sampling. Quantitative method is used in this research by using questioner in each research variable by using some indicators. The result of the research proves that Audit Competence has a positive effect on audit quality and integrity of auditor positively to audit quality.